Comparative Study of Al-Ghazali and Ibn Arabi's Theodicy Thoughts About Divine Love - Syah, Yoshy Hendra Hardiyan; Kuswana, Dadang; Qomaruzzaman, Bambang (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
This research discusses the Covid-19 virus as an example of a case of suffering from the problematics of Theodicy, because Covid-19 has claimed lives, suffered economically, socially and academically, so that it appears that God is not all-just, not all-loving and not all-merciful. This research is qualitative research using descriptive analysis methods and comparative methods. This type of research is a literature review (Library Research) which uses a philosophical approach, and uses theodicy theory in the Covid-19 case. Primary data sources in this research include the works of Ibn Arabi, namely "al-Futuhat al-Makkiyah". Meanwhile, in Al-Ghazali's work, namely "Ihya Ulumuddin" part "Al-Mahabbah wa asy-Syauq wa al-Uns wa ar-Ridha". The results of this research are that Ibn Arabi and Al-Ghazali both answered that the Covid-19 suffering incident that was revealed by God to humans was not a form of wrath or punishment from God so that He is claimed to be God who is not Most Just, Not Most Merciful, and not all-loving, but as a manifestation of God, all-good, all-just, full of love and affection for His servants. However, the two have differences, namely in their path (the focal point of thought), Ibn Arabi's thinking which has a Sufistic pattern, namely on the basis of "Divine Love" with the focal point of adhering to the unity of existence (Wahdat al-Wujud). Meanwhile, in Al-Ghazali's thought, the style of his discussion is more Sufi in nature, namely on the basis of "Divine Love" with a focus on knowledge of God.